High-resolution lidar observations of sedimentation-induced size sorting of droplets near a laboratory cloud top - Fan Yang; Yong Meng Sua; Zipei Zheng; Jesse Anderson; Hamed Fahandezh Sadi; Jae Min Yeom; Suryadev Pratap Singh; Pei Hou; Will H. Cantrell; Ernie R. Lewis; Alex B. Kostinski; Raymond A. Shaw (Proceedings of the National Academy of Sciences, 2025)
Cloud optical properties and precipitation, which are crucial to weather and climate, are strongly influenced by cloud microphysical properties that are still poorly understood. Here, we develop a high-resolution time-correlated single-photon-counting lidar and apply it to observe cloud microphysical properties at one-centimeter range resolution in a convection chamber under well-controlled conditions. Together with concurrent in-situ measurements and theoretical analysis, our lidar observations indicate that although turbulent mixing tends to homogenize the cloud in the bulk region, entrainment and sedimentation cause inhomogeneities in droplet concentrations near the cloud top. Specifically, the topmost region is directly affected by entrainment, and lidar profiles show clear evidence of entrained air and detrained cloud filament. The transition region below exhibits vertical size sorting of cloud droplets caused by sedimentation. Our results suggest that using a single sedimentation velocity for all cloud droplets, as is done in many atmospheric models, overlooks key physics relevant to the microphysical structure near the cloud top. Our conceptual model used to describe these measurements can serve as a step toward improving the current modeling of processes in the cloud top region.